Marja’ al-Taqlīd dan Proyek Syiahisasi di Indonesia - Kurniawan, Muhammad Irfanudin; Pratama, Arizqi Ihsan; Abdurrahman, Usamah (Tasfiyah: Jurnal Pemikiran Islam, 2022)
This article tries to discuss how Syiah influence people in Indonesia to follow them. If their influence has expanded, Syiah will try to create Marja’ al-Taqlīd. By creating Marja’ al-Taqlīd, Syiahâ€™s movement in Indonesia will be directly connected to the WilÄyat al-FaqÄ«h system in Iran which is under the leadership of Ali Khameini as Waly al-FaqÄ«h, the highest ruler of government and religious authority. If this happens, the integrity and sovereignty of the Republic of Indonesia will be in danger. This article aims to reveal the Syiaization process that occurred in Indonesia which led to the creation of Marja’ al-Taqlīd. The author tries to collect the factors that cause the development of Syiahâ€™s movement in this country with a majority population of Sunnis. By using qualitative methods and in-depth understanding, the authors collect data through interviews, observations, and documentation studies. As a result, the authors found several factors causing the massive movement of Syiahâ€™s teachings in Indonesia. Among the causative factors that exist are Muslims less knowledge of their religion, plus the lack of knowledge about Shiaâ€™s teachings. The economic weakness of Muslims is also well utilized by Syiah to launch their mission. The Moslem scholars of Sunni also did not move quickly to counter Syiahâ€™s mission. In addition, the Syiahâ€™s movement also seems to have received defense and support from the government and is still considered a part of Islam.